A Study on Repositioning Nalidixic Acid via Lanthanide Complexation: Synthesis, Characterization, Cytotoxicity and DNA/Protein Binding Studies - Ana-Madalina Maciuca; Alexandra-Cristina Munteanu; Mirela Mihaila; Mihaela Badea; Rodica Olar; George Mihai Nitulescu; Cristian V. A. Munteanu; Valentina Uivarosi (MDPI AG, 2022)
"Drug repositioning" is a modern strategy used to uncover new applications for out-of-date drugs. In this context, nalidixic acid, the first member of the quinolone class with limited use today, has been selected to obtain nine new metal complexes with lanthanide cations (La3+, Sm3+, Eu3+, Gd3+, Tb3+); the experimental data suggest that the quinolone acts as a bidentate ligand, binding to the metal ion via the keto and carboxylate oxygen atoms, findings that are supported by DFT calculations. The cytotoxic activity of the complexes has been studied using the tumoral cell lines, MDA-MB-231 and LoVo, and a normal cell line, HUVEC. The most active compounds of the series display selective activity against LoVo. Their affinity for DNA and the manner of binding have been tested using UV-Vis spectroscopy and competitive binding studies; our results indicate that major and minor groove binding play a significant role in these interactions. The affinity towards serum proteins has also been evaluated, the complexes displaying higher affinity towards albumin than apotransferrin.